Lesional psychiatric neurosurgery: meta-analysis of clinical outcomes using a transdiagnostic approach. Issue 2 (14th July 2021) - Davidson, Benjamin; Eapen-John, David; Mithani, Karim; Rabin, Jennifer S; Meng, Ying; Cao, Xingshan; Pople, Christopher B; Giacobbe, Peter; Hamani, Clement; Lipsman, Nir
Abstract : Background: Four ablative neurosurgical procedures are used in the treatment of refractory psychiatric illness. The long-term effects of these procedures on psychiatric symptoms across disorders has never been synthesised and meta-analysed. Methods: A preregistered systematic review was performed on studies reporting clinical results following ablative psychiatric neurosurgery. Four possible outcome measures were extracted for each study: depression, obsessive–compulsive symptoms, anxiety and clinical global impression. Effect sizes were calculated using Hedge's g. Equipercentile linking was used to convert symptom scores to a common metric. The main outcome measures were the magnitude of improvement in depression, obsessive compulsive symptoms, anxiety and clinical global impression. The secondary outcome was a subgroup analysis comparing the magnitude of symptom changes between the four procedures. Results: Of 943 articles, 43 studies reporting data from 1414 unique patients, were included for pooled effects estimates with a random-effects meta-analysis. Results showed that there was a large effect size for improvements in depression (g=1.27; p<0.0001), obsessive–compulsive symptoms (g=2.25; p<0.0001) and anxiety (g=1.76; p<0.0001). The pooled clinical global impression improvement score was 2.36 (p<0.0001). On subgroup analysis, there was only a significant degree of heterogeneity in effect sizes between procedure types for anxiety symptoms, with capsulotomy resulting in a greater reduction in anxiety than cingulotomy. Conclusions: Contemporary ablative neurosurgical procedures were significantly associated with improvements in depression, obsessive–compulsive symptoms, anxiety and clinical global impression. PROSPERO registration number: CRD42020164784.